Proyecto de inversión para la implementación de una franquicia de comida rápida "Carbón Burguer" en la ciudad de Catamayo - Villavicencio Erazo, Jonathan Israel (2016)
This thesis is mainly based on the importance of entrepreneurship on the economy of a country, therefore, being an investment project that is directed to the needs of a human need identified in the city of Catamayo, for which a general objective proposed four specific objectives were developed as follows: The first goal was: To develop a market study to determine the likelihood of success of the investment proposal which was met through the use of surveys to help; define both the supply and the demand in the market and develop a marketing plan that allows the insertion of the product on the market. The second stated objective was: To determine the technical feasibility of implementing a fast food franchise "COAL BURGUER" in the city of Catamayo; This developed after seeing delimited installed and used capacity, then the macro and micro location and project engineering; in which knowledge is put implements, which is required for local franchise and so have a good performance. 5 The third objective set "Develop an administrative and legal study to substantiate the organizational structure of the investment project for the implementation of a fast food franchise" COAL BURGUER "in the city of Catamayo; here it is given to know the legal procedures, necessary operating permits and organizational design; likewise defining a manual of staff functions. The fourth objective "establish the economic and financial feasibility of the investment project to determine the feasibility"; in which the values of investments in fixed assets and working capital deferred specified for the purpose of calculating revenue and cost projections, cash flow, calculation of economic indicators such as net present value, internal rate of return, Cost / Benefit, Period Payback, Breakeven and Sensitivity coefficient giving a positive result when implementing this franchise. To carry out the work was done using different methods such as: scientific, inductive, deductive, analytical, synthetic, mathematical and statistical techniques such as observation, sampling, interview, survey and bibliography; and schedules are backing some relevant information of the thesis. To end this thesis it was concluded that the investment project is viable as financial study results are positive so that you can implement local sales of coal burger franchise in the city of Catamayo.